Избранное: рассказы, повести / Ю. Н. Куранов - Куранов Юрий Николаевич (Советский писатель, 1984)
Экземпляры: Ф-13 (ретроконверсия) / Инвентарный номер: 10688 / Цена: 2.70 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6